Inverse Association Between Serum Non–High‐Density Lipoprotein Cholesterol Levels and Mortality in Patients Undergoing Incident Hemodialysis. Issue 12 (19th June 2018) - Chang, Tae Ik; Streja, Elani; Ko, Gang Jee; Naderi, Neda; Rhee, Connie M.; Kovesdy, Csaba P.; Kashyap, Moti L.; Vaziri, Nosratola D.; Kalantar‐Zadeh, Kamyar; Moradi, Hamid
Abstract : Background: There is accumulating evidence that serum levels of non–high‐density lipoprotein cholesterol (non–HDL‐C) are a more accurate predictor of cardiovascular outcomes when compared with low‐density lipoprotein cholesterol. However, we recently found that higher serum concentrations of triglycerides are associated with better outcomes in patients undergoing hemodialysis. Therefore, we hypothesized that the association of serum levels of non–HDL‐C (which includes triglyceride‐rich lipoproteins) with outcomes may also be different in patients undergoing hemodialysis when compared with other patient populations. Methods and Results: We studied the association of baseline and time‐dependent serum levels of non–HDL‐C with all‐cause and cardiovascular mortality using Cox proportional hazard regression models in a nationally representative cohort of 50 118 patients undergoing incident hemodialysis from January 1, 2007, to December 31, 2011. In time‐dependent models adjusted for case mix and surrogates of malnutrition and inflammation, a graded inverse association between non–HDL‐C level and mortality was demonstrated with hazard ratios (95% confidence intervals) of the lowest (<60 mg/dL) and highest (≥160 mg/dL) categories: 1.88 (1.72–2.06) and 0.73 (0.64–0.83) for all‐cause mortality and 2.07 (1.78–2.41) and 0.75 (0.60–0.93) for cardiovascular mortality, respectively (reference, 100–115 mg/dL). In analyses using baseline values, non–HDL‐C levels <100 mg/dL were also associated with significantly higher mortality risk across all levels of adjustment. Similar associations were found when evaluating non‐HDL/HDL cholesterol ratio and mortality, with the highest all‐cause and cardiovascular mortality being observed in patients with decreased non‐HDL/HDL‐C ratio (<2.5). Conclusions: Contrary to the general population, decrements in non–HDL‐C and non‐HDL/HDL cholesterol ratio were paradoxically associated with increased all‐cause and cardiovascular mortality in patients undergoing incident hemodialysis. The underlying mechanisms responsible for these associations await further investigation.